2005
DOI: 10.1590/s0365-05962005000200008
|View full text |Cite
|
Sign up to set email alerts
|

Borreliose de Lyme simile: uma doença emergente e relevante para a dermatologia no Brasil

Abstract: This review article presents diseases related to spirochetes of the genus Borrelia, which are the etiological agents of many human and animal diseases. Focus was given to the Borrelia burgdorferi sensu lato complex, including nine different species that cause diseases often with multisystemic involvement and raising interest to many medical specialties, such as Dermatology, Rheumatology, Cardiology and Neurology. Due to differences concerning the etiologic agent, clinical and laboratorial presentations, when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
0
8
0
12
Order By: Relevance
“…Also, skin lesions are not restricted to the presence of EM or annular secondary lesion. Localized scleroderma-like lesion, benign B lymphocytoma, acrodermatitis chronica atrophicans (ACA) and panniculitis have been described in Brazil 15,47 . All these symptoms already identified in BYS, must be remembered by Brazilian physicians when they are performing a patient's anamnesis and physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Also, skin lesions are not restricted to the presence of EM or annular secondary lesion. Localized scleroderma-like lesion, benign B lymphocytoma, acrodermatitis chronica atrophicans (ACA) and panniculitis have been described in Brazil 15,47 . All these symptoms already identified in BYS, must be remembered by Brazilian physicians when they are performing a patient's anamnesis and physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found adherence and development of spirochetes to the cells of R. microplus and A. cajennense. The development of this type of study is important because these ticks are involved in the transmission of spirochetes of the genus Borrelia in Brazil (Fonseca et al, 2005;Mantovani et al, 2007;Yoshinari et al, 2010). Rezende et al (2008) demonstrated the occurrence of Borrelia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Estes microrganismos apresentam distribuição global e já foram descritos para-sitando diversos grupos de aves em praticamente todas as regiões geográficas (Fudge 2000, Santos-Prezoto et al 2004, Fonseca et al 2005, Lisbôa et al 2008, Fecchio 2011. Dentre os parasitos, chama-se atenção para o gênero Plasmodium (Marchiafava & Celli, 1885), causador da malária aviária, que até 2005, foi registrado em 13,5% da avifauna mundial analisada para hemoparasitos.…”
Section: Introductionunclassified
“…No mundo, a borreliose aviária é ocasionada por Borrelia anserina, que delineia um quadro clínico inicial de hipertermia e polidipsia, sonolência, inapetência, diarreia verde-escura, com evolução para cianose com hipotermia, podendo ocorrer transtornos paralíticos e morte (Fonseca et al 2005, Ataliba et al 2007, Lisbôa et al 2008.…”
Section: Introductionunclassified